Potential Contribution of Type I Alveolar Epithelial Cells to Chronic Neonatal Lung Disease - Rozycki, Henry J. (Frontiers in Pediatrics, 2014)
The alveolar surface is covered by large flat Type I cells (alveolar epithelial cells 1, AEC1). The normal physiological function of AEC1s involves gas exchange, based on their location in approximation to the capillary endothelium and their thinness, and in ion and water flux, as shown by the presence of solute active transport proteins, water channels, and impermeable tight junctions between cells. With the recent ability to produce relatively pure cultures of AEC1 cells, new functions have been described. These may be relevant to lung injury, repair, and the abnormal development that characterizes bronchopulmonary dysplasia (BPD). To hypothesize a potential role for AEC1 in the development of lung injury and abnormal repair/development in premature lungs, evidence is presented for their presence in the developing lung, how their source may not be the Type II cell (AEC2) as has been assumed for 40 years, and how the cell can be damaged by same type of stressors as those which lead to BPD. Recent work shows that the cells are part of the innate immune response, capable of producing pro-inflammatory mediators, which could contribute to the increase in inflammation seen in early BPD. One of the receptors found exclusively on AEC1 cells in the lung, called RAGE, may also have a role in increased inflammation and alveolar simplification. While the current evidence for AEC1 involvement in BPD is circumstantial and limited at present, the accumulating data supports several hypotheses and questions regarding potential differences in the behavior of AEC1 cells from newborn and premature lung compared with the adult lung.